Nutritional ecology of blowflies (Diptera, Calliphoridae): estimates of critical larval weight for pupation on two different diets - Ribeiro, Cássio da Silva [UNESP]; Von Zuben, Claudio José [UNESP] (Sociedade Brasileira de Entomologia, 2010)
Em ambiente natural, as moscas-varejeiras utilizam como alimento, substratos discretos e efêmeros, como por exemplo, carcaças em decomposição. Normalmente, o nível de competição por alimento nesses substratos é bastante severo, e somente vão sobreviver os indivíduos que atingiram o peso larval crítico para pupação. Como esse valor não é conhecido para várias espécies de moscas-varejeiras, o objetivo do presente trabalho foi de obter esse peso crítico para quatro espécies de moscas-varejeiras dos gêneros Chrysomya e Lucilia, em dois tipos de substrato alimentar: dieta artificial e carne bovina moída. Os pesos críticos geralmente se situaram na faixa de 30 a 35 mg. O menor peso larval que permitiu a pupação foi de 30,0 mg em C. megacephala criada em carne bovina moída. Esta espécie também foi a mais adaptada a empupar com pesos larvais baixos em relação ao peso larval máximo para machos. Já a fêmea melhor adaptada a empupar foi uma C. albiceps com peso crítico representando 39,20 % do máximo obtido. Os menores pesos críticos que deram origem a pupas foram observados em fêmeas, para todas as espécies e dietas, representando provavelmente uma estratégia evolutiva que procura privilegiar a sobrevivência das fêmeas, responsáveis pela formação dos ovos, contribuindo para a formação das futuras gerações. Já com relação à perda em porcentagem, de biomassa do adulto em relação às respectivas larvas de terceiro instar, em C. megacephala as fêmeas perderam menos peso que os machos em ambas as dietas, sendo que para C. albiceps e L. cuprina, isto ocorre com os machos.

Under natural environmental conditions, blowflies utilize discrete and ephemeral feeding resources such as decaying carcasses. Competition for food on such feeding substrates is usually very severe, and only the individuals that are capable of attaining the critical larval weight for pupation will be able to survive. This critical weight is hitherto unknown for several blowfly species; therefore, the current work is aimed at obtaining such a critical value for four blowfly species of the genera Chrysomya and Lucilia, deploying two types of feeding substrate, namely, artificial diet and macerated bovine meat. on the whole, the critical weights ranged from 30 to 35 mg. The lowest larval weight which permitted pupation was 30.0 mg for Chrysomya megacephala reared on macerated bovine meat. This species was also the best adapted to pupation at low larval weights in relation to the maximum larval weight for males. Regarding the pupation of females, the best-adapted individual was a C. albiceps specimen exhibiting a critical weight that was equal to 39.20 % of the maximum value obtained. Concerning all the species and diet types, the female individuals exhibited the lowest critical weights that produced viable pupae, probably representing an evolutionary strategy that favoured the survival of females, responsible for the egg formation, contributing to the establishment of future generations. Regarding the loss (in percentage) of adult biomass in relation to the third instar larvae, the females of C. megacephala lost less weight than males in both feeding substrates. on the other hand, such a loss of weight occurred in males of C. albiceps and L. cuprina.
Ecologia nutricional de moscas-varejeiras (Diptera, Calliphoridae): estimativas de peso larval crítico para pupação em duas diferentes dietas
Keywords: Alimento; califorídeos; competição; larvas; peso mínimo; Calliphorids; competition; food; larvae; minimum weight